Our lives, our fortunes, our sacred honor [videorecording] - Craig, Scott; Harvey, Lynne (New York Lynne Harvey Production for Trots Corporation, 1992)
A look at Americans who pledged their lives and fortunes, their sacred honor for liberty.
VHS.
Editor, Bill Arnold.
Keywords: United States -- Biography; Heroes -- United States; Success -- United States; United States -- History